MEASURING THE QUALITY OF END OF LIFE USING ICECAP SCM: FEASIBILITY AND ACCEPTABILITY. Issue 1 (1st March 2014) - Bailey, CJ; Orlando, R; Kinghorn, P; Armour, K; Perry, R; Coast, J
Abstract : Introduction: Measuring the quality of end-of-life with generic health instruments has received criticism amongst palliative care researchers. The ICECAP Supportive Care Measure (ICECAP-SCM) is a self-complete questionnaire developed to evaluate palliative and supportive care. Using attributes involving autonomy, love, physical and emotional suffering, dignity, support and preparation, the instrument measures patients' wellbeing in terms of 'capability' when they are receiving supportive care. Aim(s) and method(s): To determine the feasibility of completion and the acceptability of the ICECAP-SCM amongst people receiving supportive care and their potential proxies. Using the 'think-aloud' technique, participants were asked to verbalise their thoughts whilst completing the ICECAP-SCM. This was followed by an exploration of the process of completion. All interviews were transcribed verbatim. Constant comparative methods were used to analyse the semi-structured data. Results: Measuring the end of life is complex due to the 'adaptive normality' that patients experience as their illness trajectory changes. Despite this, the attributes of the ICECAP-SCM offer a comprehensive overview of quality of end of life to capture and measure capability. It is easy to conduct in a hospice setting and easily understood by participants, including patients who are very near the end of life. It is perceived as an appropriate measure by patients receiving supportive care and one that is able to accurately and appropriately record their quality of life. Conclusion(s): ICECAP-SCM is feasible for use at end of life and acceptable to patients and proxies. Subject to further investigation of validity and reliability, it appears to offer a promising means of evaluating interventions at the end of life.